The invisibilization of the LGBTQIA+ population in the pandemic context of covid-19: reflections on biopolitics, necropolitics and intersectionality - Moraes, Morgana Naiara Barbosa; Fernandes, Luis Antonio Bitante [UNESP] (Univ Federal Espirito Santo, 2023)
From the perspective of the concepts of biopower, biopolitics and necropolitics, as devices of power, we analyze and describe the invisibility of abject bodies in the context of the covid-19 pandemic in Brazil. After creating a dialogue between the aforementioned concepts, bringing them closer to decolonial thinking, regarding the intersectionality between race, class, gender and sexuality, we analyzed data on the impact of the covid-19 pandemic that were provided by two civil organizations linked to the protection of the LGBTQIA+ population, by ANTRA and the #VoteLGBT Collective. We demonstrate that these data denounce the ills caused by the pandemic and that the absence of public policies aimed at protecting the bodies of this population demonstrates that the Brazilian State determines who will live and who will die.
Keywords: necropolitics; abject bodies; pandemic; sexuality